Protecting All Children's Teeth (PACT): Oral Habits - Melinda Clark; David Krol (Association of American Medical Colleges, 2014)
Abstract Protecting All Children's Teeth (PACT) was created by the AAP Oral Health Initiative to educate medical students, residents, pediatric primary care providers, and others interested in infant, child, and adolescent health about the importance of oral health in overall health. The curriculum provides in depth coverage of child oral health, oral health guidance, and preventive care to increase comfort in recognizing dental disease and conditions and communicate with dental professionals. The 13 modules of the PACT training program comprehensively address oral health promotion, disease prevention, diagnosis, and treatment of oral health disease in children. Oral habits, including nonnutritive sucking, teeth grinding (bruxism), and nail biting, are extremely common in children and are often a source of concern for families and questions for pediatricians. The information provided in this presentation is intended to help health professionals appropriately reassure parents, address concerns and intervene when necessary. The PACT Oral Health Curriculum has been in use since 2007 by physicians in training at the medical school and residency levels, as well as those in clinical practice. The content has been used by Pediatric, Family Medicine and Emergency Medicine physician training programs, as well as by Physician Assistants, Nurse Practitioners, Nurses, Dentists and Dental Hygienists in training and in clinical practice.